Induction of Labour in Prelabour Rupture of Membranes with or without Cervical Ripening with Prostaglandin E2: A Randomized Controlled Trial - Aryal, Shreyashi; Karki, Chandra (Journal of Lumbini Medical College, 2016)
Objective: To compare the outcome of induction of labour with titrated dose of oxytocin with or without pre induction cervical ripening using prostaglandin E2. Methods: This is a prospective study. Sixty women with prelabour rupture of membranes (PROM) and Bishops score of less than six were randomly assigned to either immediate induction with intravenous oxytocin drip or induction with intravenous oxytocin drip preceded by cervical priming with prostaglandin E2 (PGE2) gel 0.5mg instilled intracervically. These two groups were compared regarding the mode of delivery, induction to delivery interval and maternal and neonatal morbidities. Results: Cervical priming with PGE2 resulted in lesser number of caesarean section (5 Vs. 12) and lower incidence of meconium stained liquor (n=6 Vs. n=2). Induction to vaginal delivery interval was shorter when cervical priming was done (5.4 hrs Vs 7.9 hrs). The maternal morbidity was negligible (<1%) in both the groups. The number of neonates with birth asphyxia (n=2) and the need for their resuscitation (n=2) was more in the oxytocin group but the need of antibiotics for the neonates was more in PGE2 group (5% Vs. 3%). Conclusion: Induction of labor with oxytocin, with or without cervical priming with vaginal PGE2 gel, are both reasonable options in cases of PROM, since they result in statistically non significant rates of maternal and neonatal morbidities and caesarean section. Cervical priming with prostaglandin results in higher rate of vaginal delivery and shorter induction to vaginal delivery interval and this is viewed as an advantage to the mother. Journal of Lumbini Medical College. 2014;2(1):4-9.